A note on Myrberg points and ergodicity - Falk, Kurt (MATHEMATICA SCANDINAVICA, 2005)
The main purpose of this note is to further clarify the strong relationship between ergodicity and Myrberg type dynamics in hyperbolic manifolds. This is achieved mainly via a new suggestive proof of the fact that the Myrberg limit set of a Kleinian group is of full Patterson measure if the geodesic flow on the associated hyperbolic manifold is ergodic with respect to the Patterson-Sullivan measure.